Judging or Ruling the Twelve Tribes of Israel? The Sense of Krínō in Matthew 19.28 - Lee, Yongbom (2015)
Commentators are divided about whether κρίνω in Matt 19.28 means “to judge” or “to rule.” This study seeks to discern its specific sense in this verse by exploring the semantic domains of the syntagmatic contexts in which κρίνω is used in the LXX, Philo, Josephus, and the New Testament (besides Matt 19.28; Luke 22.30) and by considering the intertextual and literary contexts of Matt 19.28. The study concludes that the sense of κρίνω in Matt 19.28 is “to judge” rather than “to rule.”
Keywords: Daniel 7; LXX; Luke 22.30; Matt 19.28; κρίνω; Intertextuality; literary context; semantic domain; syntagmatic context